Think Talk Write: An Effort to Improve Students' Information Literacy - Lailan Safitri Barus; Ummi Nur Afinni Dwi Jayanti (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to examine the effect of the Think Talk Write learning model as an effort to improve students' information literacy in the study of the concept of the immune system. This type of research includes a action research approach with a quasi-experimental method (using pre-test and post-test). The research subject was a population of 52 students in class IX science. The research data was collected based on the results of the pre-test and post-test that had been carried out on grade IX students. Based on the results of this study, it was found that the class that applied the think talk write learning model got a higher average score (4.07) than the class that applied the conventional learning model (4.05). Thus, it is concluded that learning that applies the think talk write model can improve information literacy in students.